Prarancangan Pabrik Hexamine dengan Proses Leonard Kapasitas 50.000 Ton/tahun - Aryanto, Yanur Hendra, Hamid Abdillah, S.T., M.T, Ir. Herry Purnama, M.T., Ph.D (2017)
Hexamine is useful industrial raw material, such as antiseptic in medicine, anti-caking agent for urea fertilizer, accelerator and anti-vulcanisation in rubber industry, and explosive material. The plant of hexamine with production capacity 50.000 ton/year is intended to meet the requirement of hexamine in the country and overseas. This plant will be planned on 2020 and built in Cikampek of Karawang regency. Hexamine is produced with reacting ammonia and formaldehide in continous stirred tank reactor (CSTR) in temperature 38ºC and pressure 16 atm, irreversible and eksoterm. The stage of hexamine production is include formation of hexamine, concentrating product, cristalling, and puring. In this plant, the need of formaldehide is 22.375,8895 kg/hour and the need of ammonia is 3.150,9263 kg/hour. The product of hexamine is 6.313,6738 kg/hour. Utilities for this plant are 90.995,072 kg/hour of water supply, 48.901,9767 kg/hour of steam need, 101,52m3/hour of the pressed-air need, 456,4803 kW of the electricity need gotten from 365,18 kW of generator and the remain need will be supplay by PLN, and 1.132,1345 L/hour of the diesel fuel need. In this plant also have laboratory to control quality of raw material, product, and waste water. The type of the plant is Perseroan Terbatas (PT). The working systems used in this plant are shift and non-shift with 168 employee. This hexamine plant use Rp388.868.512.539,00 as fixed capital and Rp106.047.320.467,00 as working capital. The economic analysis results of this plant show the profit each year as much as: Rp110.399.350.134,00 (before tax) and Rp77.279.545.094,00 (after tax), Return On Investment (ROI) as much as: 28,39% (before tax) and 19,87% (after tax), Pay Out Time (POT) as long as: 2,60 years (before tax) and 3,34 (after tax), Break Even Point (BEP) as much as 46,15%, Shut Down Point (SDP) as much as 22,17%, and Internal Rate Return (IRR) based on Discounted Cash Flow (DCF) as much as 37,25%. From the economic analytic we can conclude that this plant is profitable and reasonable to build. Keywords: Hexamine, Leonard, CSTR.